PENGUKURAN KANDUNGAN SKOPOLETIN PADA BEBERAPA TINGKAT KEMATANGAN BUAH MENGKUDU (Morinda citrifolia Linn) DENGAN METODE KLT DENSITOMETRI - Diana Nurus Sholehah (Agrovigor, 2010)
Morinda citrifolia fruit has been used as remedies in Indonesia because many diseases could be healed. Scopoletin, one of major component of Morinda citrifolia was chosen as  marker compound because of  its various activites such as  hypotensive, antiinflamatory and antihistamine. The research aimed to determinate scopoletin in some maturations stage of Morinda citrifolia fruit in order to get best fruit for traditional medicine and phytopharmaca with optimal therapeutical effect . A simple and reliable TLC-Densitometry which has been validated before, was choosen to this aim. Fruit at stage 1,2,3 and 4 were taken  20, 45, 105 and 120 days after flowering. TLC was held on silica gel plates as stationary and ether : toluene : acetic acid 10 % (58:45:0,4) as mobile phase of fruit at stage 1, 2 and 4 and also ether : toluene : acetic acid 10 % (58:45:0,8) as mobile phase of fruit at stage 3.  Mean concentration of scopoletin at stage 1 was found to be (10,72±0,45) ppm, stage 2 was found to be (19,19±0,68) ppm, stage 3 found to be (57,94±0,79) ppm and stage 4 (14,11±0,39) ppm respectively.